Hubungan Antara Motivasi Dengan Kepuasan Kerja Perawat Di Puskesmas Wajak Kabupaten Malang Tahun 2024: Hubungan Antara Motivasi Dengan Kepuasan Kerja Perawat Di Puskesmas Wajak Kabupaten Malang Tahun 2024 - Kirono, Indung Susilo Sekti (Jurnal Keperawatan Muhammadiyah, 2026)
Methods: This research is an analytical study with a cross-sectional method. Sampling in this study used the total sampling technique with a sample size of 30 respondents. The correlation test used in this study is the Spearman test. Results: In this survey, those with the highest level of work motivation were 24 (84.7%) respondents and only 6 (15.3%) respondents with low motivation with the highest job satisfaction with a satisfied category of 30 (100%). There is a significant relationship between job satisfaction and work motivation at the Wajak Health Center UPT with a p value of 0.000 (p value <0.05) which indicates that the correlation value is significant and the Spearman correlation coefficient value is 0.542. Conclusion: There is a significant relationship between the study of the relationship between work motivation and the level of nurse job satisfaction at the Wajak Health Center